Who should bear the cost of China's carbon emissions embodied in goods for exports? - ZhongXiang Zhang (Fondazione Eni Enrico Mattei (FEEM), 2011)
China's capital-intensive, export-oriented, spectacular economic growth since launching its open-door policy and economic reforms in late 1978 not only has created jobs and has lifted millions of the Chinese people out of poverty, but also has given rise to unprecedented environmental pollution and CO2 emissions. While estimates of the embedded CO2 emissions in China's trade differ, both single country studies for China and global studies show a hefty chunk of China's CO2 emissions embedded in trade. This portion of CO2 emissions had helped to turn China into the world's largest carbon emitter, and is further widening its gap with the second largest emitter. This raises the issue of who should be responsible for this portion of emissions and bearing the carbon cost of exports. China certainly wants importers to cover some, if not all, of those costs. While China's stance is understandable, this paper has argued from a broad and balanced perspective that if this is pushed too far, it will not help to find solutions to this issue. On the contrary it can be to China's disadvantage for a number of reasons. However, aligning this responsibility with China does not necessarily suggest the sole reliance on domestic actions. In that context, the paper recommends specific actions that need to be taken internationally as well as domestically in order to effectively control the embedded CO2 emissions in China's trade.
Keywords: F18; P28; Q42; Q43; Q48; Q53; Q54; Q56; Q58; 330; Carbon Emissions Embodied In Trade; Consumption-Based Accounting; Production-Based Accounting; Processing Trade; Carbon Tariffs; Energy Policy